COMPARATIVE CHARACTERISTICS OF INPATIENT AND OUTPATIENT CARDIAC REHABILITATION IN PATIENTS AFTER ACUTE CORONARY SYNDROME - Pysana, B.O.; Teslenko, Yu.V.; Bilash, S.M.; Chaikina, N.O. (World of Medicine and Biology, 2025)
Cardiovascular diseases remain the leading cause of mortality in Ukraine, so effective rehabilitation after acute coronary syndrome is essential for restoring health and preventing repeat events. The purpose of the study was to compare the effectiveness of the inpatient and outpatient stages of cardiac rehabilitation. 60 patients after acute coronary syndrome who underwent various recovery programs were examined. Exercise tolerance, left ventricular ejection fraction, resting heart rate, anxiety level, quality of life, and treatment adherence were assessed. Inpatient rehabilitation improved clinical outcomes and increased therapy adherence, while outpatient rehabilitation contributed to further improvements in physical condition, emotional balance, and quality of life. Combining both stages into a single continuous system provides a sustained rehabilitation effect and increases treatment effectiveness.
Keywords: acute coronary syndrome; cardiac rehabilitation; inpatient stage; outpatient stage; treatment adherence